British images of Germany : admiration, antagonism & ambivalence, 1860 - 1914 - Scully, Richard (Britain and the world, 2012)
Introduction: The Beginnings -- Mapping Germany, 1860-1914 -- From "Geographical Expression" to German Empire -- "North Sea" or "German Ocean"? : Britain and Germany in the Wider World -- A "Pink Link" : Race, Religion and the Anglo-German Cartographic Freemasonry -- War and the Severing of the "Pink Link" -- Part II. Travelling to Germany, 1860-1914 : A Guidebook -- Britain and Baedeker's Germany -- The Rhine, the Spas, and Beyond : in War and Peace -- Business as Usual : the 1880s and 1890s -- The Last of the Summer Holidays : Twentieth Century Travel -- Part III. Models and Monsters : English Literature and the Idea of Germany -- Learned, Indefatigable, Deep-thinking Germany... -- The German Invasion of Britain in 1872 and "What Became of the Invaders" -- Two Georges and Two Germanies : Gissing and Meredith Commence Debate -- Looking Into the Abyss.. -- Part IV. Punch, Judy and Deutsche Michael : Cartoons of Germany -- "Wilhelm in Wonderland" : Germany in the Wars of Unification -- Satiated and Satisfied : Bismarckian Germany -- "Dropping the Pilot" : Kaiser Wilhelm II and the new course -- The Coming of the 'Horrible Hun' -- Conclusions